2021
DOI: 10.1097/inf.0000000000003146
|View full text |Cite
|
Sign up to set email alerts
|

First Report of SARS-CoV-2 Detection in Cerebrospinal Fluid in a Child With Guillain-Barré Syndrome

Abstract: Underlying mechanisms on the association between severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and neurologic complications are still poorly understood. Cases of Guillain-Barré Syndrome (GBS) have been linked to the SARS-CoV-2 infection as the result of dysregulated immune response with damage in neuronal tissues. In the current report, we present the first pediatric case of GBS with detection of SARS-CoV-2 in the cerebrospinal fluid (CFS). This unique case of COVID-19-associated GBS w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 16 publications
0
45
0
8
Order By: Relevance
“…At the time of the report, the patient was undergoing motor physiotherapy to recover the persistent muscle weakness in the four extremities. The other case reported in Brazil was published by Araújo et al, 2021 [44], a 17-year-old girl who presented to the emergency with a 48-h history of low back pain, followed by weakness of the extremities. Eight days earlier, the patient presented fever, abdominal pain, and diarrhea.…”
Section: Guillain-barre Syndromementioning
confidence: 98%
See 2 more Smart Citations
“…At the time of the report, the patient was undergoing motor physiotherapy to recover the persistent muscle weakness in the four extremities. The other case reported in Brazil was published by Araújo et al, 2021 [44], a 17-year-old girl who presented to the emergency with a 48-h history of low back pain, followed by weakness of the extremities. Eight days earlier, the patient presented fever, abdominal pain, and diarrhea.…”
Section: Guillain-barre Syndromementioning
confidence: 98%
“…The age of the children ranged from 24-h to 17-years old. From the 159 patients, 38 were reported with some type of cerebrovascular disease [12][13][14][15][16][17][18][19][20][21][22], 32 with different types of encephalitis [13][14][15][26][27][28][29][30][31][32], 22 with encephalopathy [10,13,24,25], and 10 patients with Guillain-Barre syndrome [13,14,[42][43][44]. Sixty-five out of 159 patients with severe neurological manifestations, were reported with Multisystem Inflammatory Syndrome (MIS-C) [10,12,[14][15][16][17]23,32,45,50,[52][53][54] (Table 1).…”
Section: Patient Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Finsterer J, et al ( 17 ) stated in a review in which they evaluated 220 GBS patients associated with COVID-19, that there were no patients in whom SARS-CoV-2 could be detected in the CSF. In a recent case report, it was reported that SARS-CoV-2 was positive in CSF for the first time in a pediatric GBS patient ( 23 ). In our study, all 12 patients in the post-COVID-19 group were SARS-CoV-2 PCR negative in CSF and we could not find data to support the direct mechanism of injury.…”
Section: Discussionmentioning
confidence: 99%
“…With interest, we read the article by Araújo et al 1 about a 17-year-old female who was diagnosed with Guillain-Barré syndrome (GBS), and subtype acute, demyelinating inflammatory polyneuropathy, 8 days after onset of a mild coronavirus disease 2019 infection. Surprisingly, cerebrospinal fluid (CSF) investigations were positive for RNA of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2).…”
Section: To the Editorsmentioning
confidence: 99%